Proč bohemák napadá bohemáka? Etnografická studie radikální scény Bohemians 1905 - Šešín, Petr (Lidé města, 2024)
The presented paper could be understood as a critical interpretation of the relations among participants on the radical scene of Bohemians 1905 Prague football fans. It also covers the development of this scene that arose in the late nineties of previous century by adopting modern elements of the hooligans subculture and lately also the ultras movement, both from other European models. However, even if this scene is perceived from the outside as an ultra-left-wing scene, there were no studies done in this field. It is not only the established or vanished, but also the “still living” terrain, which create an opportunity for ethnographic research. The chosen ethnographic approach is able to explain questions from the participants’ perspective, and therefore should help to better comprehend this phenomena inside our culture, including radical hooligans and ultras.